Centralization of Mineral and Coal Licensing Post The Enforcement of Law Number 3 Of 2020 1 - Moch. Rahmatullah Al Amin (Universitas Airlangga, 2026)
Indonesia is an archipelagic country that has many tectonic plates along its territory. This makes Indonesia a country with abundant mineral and coal resources. Thus, the mineral and coal mining industry has developed quite rapidly to date. Lots of mining companies, both local and international companies, carry out mining activities in Indonesia. Therefore, Law Number 3 of 2009 exists to regulate the activities of the mineral and coal industry in Indonesia. These laws and regulations will later be replaced by Law Number 3 of 2020 which updates many aspects of legality, especially in terms of permits. In this latest law there has been a paradigm shift from permits related to mineral and coal mining which became the authority of the regional government to issue these permits, being changed by withdrawing this authority to the central government. This implies that the authority of regional autonomy is being bypassed by the central government. So, can this help the development of mineral and coal mining or actually slow down its development? Therefore, this research will examine the impact of the new licensing regime. This research found that the centralization of mineral and coal mining permits is still not effective. Moreover, if during the implementation of the granting of the permit, the permit recipient makes a loss which affects the local community, the community cannot hold the regional government accountable.